Re-imagining business ethics meaningful solutions for a global economy - Pava, Moses L.; Primeaux, Patrick; Emerald eBooks (Amsterdam ; Boston : Elsevier, 2002)
Each of the articles in this volume, authored by researchers from around the world, focuses on new and emerging issues in business and organizational ethics. In every case, the authors offer creative insights and new perspectives.
Ethics, economics, and service : changing cultural perspectives / Rogene A. Buchholz, Sandra B. Rosenthal -- Business ethics and e-commerce in contemporary society / Kenneth Smith, John Paul Kawalek -- From imagination to realization : a legal foundation for stakeholder theory / Tara J. Radin -- Organizational misbehavior : hypotheses, research and implications / Yoav Vardi, Ely Weitz -- Moral activism and value harmonization in an integrating global economy / Duane Windsor -- Examining the impact of technology on social responsibility practices / Victoria E. Johnson, Linda L. Brennan -- Fit and misfit between codes of conduct and reality in management consulting / Marjatta Maula, Flemming Poulfelt -- A model of employees' responses to corporate volunteerism / Debra R. Comer, Elizabeth A. Cooper -- The fate of non-economic man / Michael Schwartz.
Includes bibliographical references.
Description based on print version record.
Keywords: Business ethics; Organizational behavior; Globalization; Business & Economics -- Business Ethics; Psychology -- Applied Psychology; Business ethics; Electronic books